Non-linear association and benchmark dose of blood pressure on carotid artery intima-media thickening in a general population of southern China - Qin, Linyuan; Wu, Xiaoyan; Tan, Chao; Zhang, Zhengbao; Li, You; Zhu, Xiaonian; Qin, Shenghua; Tan, Shengkui (Frontiers in Cardiovascular Medicine, 2024)
Background and Aims: To evaluate whether the J curve nonlinear association and departure point of between blood pressure (BP) on and carotid artery intima-media thickeningatherosclerosis (CACAIT) and to estimate the turning point of BP on CAIT.: Data of 111494 regular physical examinations for workers and retirees (18  years) that ranged from Jan 2011 to Dec 2016 were exported from the hospital information system were analyzed. The ordinary logistic regression and restricted cubic splines (RCS) logistic regression were employed to access the association of BP on CACAIT, and Bayes benchmark dose methods were used to estimate the benchmark dose as the departure point of BP measurements. All BP measurements except PP were positively associated with the risk of CA in ordinary logistic regression models (all p-values<0.001). All the pnonlinear-values of BP measurements were less than 0.05 in the RCS logistic regression models. Both systolic blood pressure (SBP) and diastolic blood pressure (DBP) had J curve associations with the risk of CACAIT at the departure turning point of around 120/72 70 mm Hg in RCS. The benchmark dose of 1% CA risk change of CAIT change was 120.64 and 72.46 mm Hg for SBP and DBP respectively.The predicted risks of CA at SBP and DBP levels of 120 and 70 mm Hg were 3.38% and 3.58% respectively. Conclusion: The J curve associations of SBP and DBP on the risk of CACAIT were observed among general population in southern China, and 120.64/72.46 mm Hg for SBP/DBP was the optimal turning point of blood pressure control target for significantly reducing the risk of CACAIT was 120/75-80mm Hg.